'Alum de glas' or 'Alymed glass'? Manuscript Reading in Book III of "The House of Fame." - Cawsey, Kathy (University of Toronto Quarterly)
A literary criticism is presented which focuses on the part 3 of the book "The House of Fame," by Geoffrey Chaucer. The third book of Chaucer's "The House of Fame" opens with a startling image. The mountain is shining in the sun, and as the dreamer comes closer, he realizes it is made entirely of ice. The image of the ice mountain carved with famous names is an image of the written word that will allow us to gain access to medieval concepts of writing and book production. The sources Chaucer uses to create his mountain and house of Fame are complex.